Diastereoselective One-Pot Synthesis of Succinimides Bearing a Chromone Unit - Teimouri, Mohammad Bagher; Asnaashari, Bita; Moayedi, Maryam; Naderi, Soheila (Synlett, 2015)
A diastereoselective synthesis of highly substituted succinimide derivatives with chromone and carboxylic ester functionalities from 3-formylchromones, Meldrum’s acid, and alkyl isocyanides in the presence of alcohols in moderate to good yields is described.
Keywords: formylchromone; isocyanide; Meldrum’s acid; succinimide